Tinjauan Hukum Islam terhadap Sikolodha Adat Galela di Halmahera Utara - Arsyad Dolosi; Muhammad Zein; Baharuddin Hi. Abdullah (Indonesian Journal of Shariah and Justice, 2022)
Marriage is the only way for humans to channel their sexual desires legally and legally in the view of religion. In Indonesia, the Marriage Law explains that marriage is considered valid if it is carried out in accordance with the teachings of their respective religions. However, apart from religious factors, there are also other factors that can color a person's wedding procession, namely the traditional factor. In Soasio Village, Galela District, North Halmahera Regency, there is a custom called Sikolodha, which is a tradition or custom to take a woman to be married off to the residence of a priest, community leader or relative of a man who wants to marry her. This study tries to raise the Sikolodha phenomenon and analyze it by using an emphasis on the aspect of Islamic law. This research use desciptive qualitative approach. The results of this study found that the occurrence of Sikolodha usually occurs due to several factors, including, requests for dowry that cannot be fulfilled, no parental blessing, forced to marry another man, and getting unwed pregnancy. Meanwhile, from the aspect of 'urf, there are Sikolodha models that can be justified and some are prohibited.